2022
DOI: 10.1186/s40364-022-00421-0
|View full text |Cite
|
Sign up to set email alerts
|

The pivotal application of patient-derived organoid biobanks for personalized treatment of gastrointestinal cancers

Abstract: Gastrointestinal cancers (GICs) occupy more than 30% of the cancer-related incidence and mortality around the world. Despite advances in the treatment strategies, the long-term overall survival has not been improved for patients with GICs. Recently, the novel patient-derived organoid (PDO) culture technology has become a powerful tool for GICs in a manner that recapitulates the morphology, pathology, genetic, phenotypic, and behavior traits of the original tumors. Excitingly, a number of evidences suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 137 publications
0
5
0
Order By: Relevance
“…Long-term in vitro culture of cell lines leads to loss of original tumor characteristics and inaccurate replication of the tumor microenvironment [ 68 ]. Patient-derived xenograft (PDX) models maintain tumor heterogeneity but face challenges such as low transplantation rates, large differences in human and mouse drug-use behavior, and a long process of drug screening [ 69 , 70 ]. The emergence of patient-derived tumor organoids (PDOs) addresses these challenges [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term in vitro culture of cell lines leads to loss of original tumor characteristics and inaccurate replication of the tumor microenvironment [ 68 ]. Patient-derived xenograft (PDX) models maintain tumor heterogeneity but face challenges such as low transplantation rates, large differences in human and mouse drug-use behavior, and a long process of drug screening [ 69 , 70 ]. The emergence of patient-derived tumor organoids (PDOs) addresses these challenges [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of their diversity and editability, PDTOs can be cryopreserved to form a biobank, 79 customized and scaled up, making them an ideal model for high‐throughput drug screening 80 . One study showed that a PDTO biobank established from metastatic gastrointestinal cancer patients could summarize the clinical response to regorafenib, palbociclib, taxane, cetuximab and TAS‐102 which can be applied in personalized medicine plans 81 .…”
Section: Pdtos and Assembloidsmentioning
confidence: 99%
“…Recently, patient‐derived cancer organoids have been considered useful tools to answer clinical questions 12 . Results of drug sensitivity tests using patient‐derived organoids have been shown to have a significant correlation with the therapeutic outcomes of patients in some models, including L‐OHP, 13–15 suggesting that patient‐derived cancer organoids may be useful in predicting the therapeutic effectiveness of cancer drugs in individual patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, patient‐derived cancer organoids have been considered useful tools to answer clinical questions. 12 Results of drug sensitivity tests using patient‐derived organoids have been shown to have a significant correlation with the therapeutic outcomes of patients in some models, including L‐OHP, 13 , 14 , 15 suggesting that patient‐derived cancer organoids may be useful in predicting the therapeutic effectiveness of cancer drugs in individual patients. Thus, if patient‐derived liver organoids could also be used to predict L‐OHP‐induced liver injury in treated patients, the risks and benefits of chemotherapy could be assessed before initiating treatment.…”
Section: Introductionmentioning
confidence: 99%